Lower extremity rotational deformities and patellofemoral alignment parameters in patients with anterior knee pain - Erkocak, Omer Faruk; Altan, Egemen; Altintas, Murat; Turkmen, Faik; Aydin, Bahattin Kerem; Bayar, Ahmet (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2016)
Purpose Anterior knee pain is a common musculoskeletal condition amongst young adult population. Lower extremity structural factors, such as increased femoral anteversion and lateral tibial torsion, may contribute to patellofemoral malalignment and anterior knee pain. The aim of this study was to evaluate the lower extremity structural factors and related patellofemoral alignment parameters that play a role in the aetiology of anterior knee pain. Methods This study involved three groups: patients with unilateral symptomatic knees ( n = 35), asymptomatic contralateral knees in the same patients and a control group ( n = 40). All subjects were physically examined, and Q-angles were measured. The lower extremities of all subjects were imaged by a very low-dose CT scan, and the symptomatic knees of patients were compared with their asymptomatic contralateral knees and with the healthy knees of controls regarding femoral anteversion, tibial torsion, sulcus angle, patellar tilt angle and lateral patellar displacement. Results Regarding the Q-angle, femoral anteversion and lateral tibial torsion, no significant differences were found between the symptomatic and asymptomatic knees, whereas significant differences were found between the symptomatic knees and controls. The symptomatic group demonstrated significantly greater sulcus angle only in 30° of knee flexion than did the controls. Conclusion Patients with unilateral anterior knee pain may have similar morphology at their contralateral asymptomatic lower extremity, and different morphology compared with healthy controls. Lower extremity rotational deformities may increase the risk of anterior knee pain; however, these deformities alone are not sufficient to cause knee pain, and may be predisposing factor rather than a direct aetiology. Level of evidence Diagnostic study, Level III.